Inherited thrombocytopenias—recent advances in clinical and molecular aspects. (2nd January 2017) - Balduini, Carlo L.; Melazzini, Federica; Pecci, Alessandro
Abstract: Since the beginning of the century, our knowledge of inherited thrombocytopenias greatly advanced, and we presently know 30 forms with well-defined genetic defects. This great advancement changed our view of these disorders, as we realized that most patients have only mild thrombocytopenia with inconspicuous bleeding or no bleeding tendency at all. However, better knowledge of inherited thrombocytopenias also revealed that some of the most prevalent forms expose to the risk of acquiring during infancy or adulthood additional disorders that endanger the life of patients much more than hemorrhages. Thus, inherited thrombocytopenias are complex disorders with quite different clinical features and prognosis. Identification of novel genes whose mutations result in low platelet count greatly advanced also our knowledge of the megakaryocyte biology and proved beyond any doubt that the defective proteins play an essential role in platelet biogenesis or survival in humans. Based on the study of inherited thrombocytopenias, we better understood the sequence of molecular events regulating megakaryocyte differentiation, maturation, and platelet release. Since nearly 50% of patients have as yet unidentified genetic or molecular mechanisms underlying their inherited thrombocytopenia, further studies are expected to reveal new clinical entities and new molecular mechanisms of platelet production.